2012
DOI: 10.1111/j.1600-0706.2012.20582.x
|View full text |Cite
|
Sign up to set email alerts
|

What are the possible benefits of small size for energy‐constrained ectotherms in cold stress conditions?

Abstract: In stressful environments, two main hypotheses have been proposed to explain the consequences of body size: (1) the absolute energy demand hypothesis (AED), which predicts that larger individuals are at a disadvantage under stressful conditions; (2) the relative efficiency hypothesis (RE), which predicts the reverse. We compared the effects of cold stress on different fitness traits of large and small individuals of the parasitoid wasp Aphidius ervi (Hymenoptera: Aphidiinae). For that, we exposed nymphs of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 69 publications
3
26
0
Order By: Relevance
“…For instance, Ismail et al . () showed that smaller individuals of the parasitoid A. ervi had better resistance to cold stress than larger wasps. Since parasitoid size is intimately linked to fitness‐related traits (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Ismail et al . () showed that smaller individuals of the parasitoid A. ervi had better resistance to cold stress than larger wasps. Since parasitoid size is intimately linked to fitness‐related traits (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are, however, consistent with the AED hypothesis which states that a winter should impose a selective pressure that favours smaller parasitoids. For instance, Ismail et al (2012) showed that smaller individuals of the parasitoid A. ervi had better resistance to cold stress than larger wasps. Since parasitoid size is intimately linked to fitness-related traits (e.g.…”
Section: Size Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, daughters of small mothers emerged with more mature eggs in their ovaries than did daughters of large mothers (Table 4). Working with Aphidius ervi Haliday, Ismail et al (2012) showed that, under stressful conditions (exposure to cold treatments), small females had more eggs at emergence relative to larger ones and inferred this to represent a shift toward a more pro-ovigenic strategy under stress. Thus, large body size may entail an initial fecundity disadvantage in L. fabarum, in addition to the host handling disadvantages detailed above.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, maternal egg size was positively correlated with progeny egg load among small females ( Figure 2B), suggesting that the negative effect on egg load may only occur above some threshold egg size. Working with Aphidius ervi Haliday, Ismail et al (2012) showed that, under stressful conditions (exposure to cold treatments), small females had more eggs at emergence relative to larger ones and inferred this to represent a shift toward a more pro-ovigenic strategy under stress. Because of the low L. fabarum survival in fourth instar hosts, our results did not permit analysis of effects of host instar on progeny egg load.…”
Section: Discussionmentioning
confidence: 99%